2018
DOI: 10.3390/md16050139
|View full text |Cite
|
Sign up to set email alerts
|

Triphlorethol A, a Dietary Polyphenol from Seaweed, Decreases Sleep Latency and Increases Non-Rapid Eye Movement Sleep in Mice

Abstract: In our previous studies, we have demonstrated that marine polyphenol phlorotannins promote sleep through the benzodiazepine site of the gamma-aminobutyric acid type A (GABAA) receptors. In this follow-up study, the sleep-promoting effects of triphlorethol A, one of the major phlorotannin constituents, were investigated. The effect of triphlorethol A on sleep-wake architecture and profiles was evaluated based on electroencephalogram and electromyogram data from C57BL/6N mice and compared with the well-known hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Although has being a technique used to analyze crude extracts or fractions, in order to confirm the reliability of spectrophotometric analysis (as discussed above), NMR has been also used in the identification (or confirmation) of isolated phenolic compounds [21,27,156,176], as well as of isolated phlorotannins [32,33,43,45,46,60,62,73,101,115,116,153,154,[177][178][179]184,189,207,[215][216][217]. In fact, NMR analysis has allowed to identify different groups of isolated phlorotannins, in particular, phlorethols, fuhalols, fucols, fucophlorethols, and eckols [32,33,40,43,45,46,60,62,73,153,154,[177][178][179]184,207,[215][216][217].…”
Section: Nmr Analysis Of Isolated Phenolic Compounds From Macroalgae mentioning
confidence: 99%
“…Although has being a technique used to analyze crude extracts or fractions, in order to confirm the reliability of spectrophotometric analysis (as discussed above), NMR has been also used in the identification (or confirmation) of isolated phenolic compounds [21,27,156,176], as well as of isolated phlorotannins [32,33,43,45,46,60,62,73,101,115,116,153,154,[177][178][179]184,189,207,[215][216][217]. In fact, NMR analysis has allowed to identify different groups of isolated phlorotannins, in particular, phlorethols, fuhalols, fucols, fucophlorethols, and eckols [32,33,40,43,45,46,60,62,73,153,154,[177][178][179]184,207,[215][216][217].…”
Section: Nmr Analysis Of Isolated Phenolic Compounds From Macroalgae mentioning
confidence: 99%
“…Other studies found that different polyphenols modulated sleep via GABA receptors. Polyphenols such as phlorotannins [203,204] and triphlorethol A (seaweed polyphenols) [216], red cabbage extracts [217], and kiwifruit extracts [206] decreased SOL and increased sleep duration via GABA receptors in mice. Other polyphenols such as bioflavonoids extracts from Rhus parviflora referred as Tintidikah, a medicinal plant used in south Asia, were the most potent components in decreasing SOL and increasing sleep duration via GABA receptors [205].…”
Section: Mechanisms For the Relationship Between Sleep And Fruit Amentioning
confidence: 99%
“…Triphlorethol A, one of the most important components of phlorotannins, shows a dose-dependent decrease of sleep latency in C57BL/6N mice. Results show that triphlorethol A obtained from seaweed is comparable to zolpidem, a well-known hypnotic drug (Yoon and Cho, 2018).…”
Section: Insomniamentioning
confidence: 90%